Impact of Perioperative Antibiotic Prophylaxis Targeting Multidrug-Resistant Gram-Negative Bacteria on Postoperative Infection Rates in Liver Transplant Recipients - Eleni Massa; Dimitrios Agapakis; Kalliopi Tsakiri; Nikolaos Antoniadis; Elena Angeloudi; Georgios Katsanos; Vasiliki Dourliou; Antigoni Champla; Christina Mouratidou; Dafni Stamou; Ioannis Alevroudis; Ariadni Fouza; et al. (Diagnostics)
Infections with multidrug-resistant (MDR) organisms remain a significant cause of morbidity and mortality among liver transplant recipients, despite advances in surgical techniques and immunosuppressive therapy. This prospective observational study aimed to evaluate the impact of targeted perioperative antibiotic prophylaxis against MDR Gram-negative bacteria on postoperative infections and mortality in liver transplant recipients. Seventy-nine adult patients who underwent liver transplantation and were admitted to the ICU for more than 24 h postoperatively were included. Demographics, disease severity scores, comorbidities, and lengths of ICU and hospital stay were recorded. Colonization with carbapenem-resistant Gram-negative bacteria was assessed via preoperative and postoperative cultures from the blood, urine, rectum, and tracheal secretions. Patients were divided into two groups: those with MDR colonization or infection who received targeted prophylaxis and controls who received standard prophylaxis. Infectious complications (30.4%) occurred significantly less frequently than non-infectious ones (62.0%, p = 0.005). The most common infections were bacteremia (22.7%), pneumonia (17.7%), and surgical site infections (2.5%), with most events occurring within 15 days post-transplant. MDR pathogens isolated included Klebsiella pneumoniae, Acinetobacter baumannii, and Pseudomonas aeruginosa. Although overall complication and mortality rates at 30 days and 3 months did not differ significantly between groups, the targeted prophylaxis group had fewer infectious complications (22.8% vs. 68.5%, p = 0.008), particularly bacteremia (p = 0.007). Infection-related mortality was also significantly reduced in this group (p = 0.039). These findings suggest that identification of MDR colonization and administration of targeted perioperative antibiotics may reduce septic complications in liver transplant patients. Further prospective studies are warranted to confirm benefits on outcomes and resource utilization.